EVALUASI KUALITAS WEBSITE DITINJAU DARI KEPUASAN USER DENGAN WEB ANALYTIC (STUDI KASUS PADA WEBSITE MAJALAH LIVINGETC INDONESIA) - Ming, Kim (Institute of Research and Community Outreach - Petra Christian University, 2014)
The purpose of this study is to evaluate livingetcindonesia.com website, in order to improve user satisfaction as an online media and the extent to which the level of user satisfaction to the presentation of the website. The website criteria: perceived usefulness, ease of use, ease of finding information, and the design/layout of page is examined to determine the effect on user satisfaction. Analysis of site infrastructure has been meeting the needs of web and database servers, database structure, web analytics to determine the user visits the website and area/location where a user visiting the website. The survey results showed variable Perceived usefullness, Ease of use, Ease of finding information, and Design/Layout of page significant effect on user satisfaction.